Odor control pulp composition
By adding low-quality copper ions and metal salt catalysts to the fluff pulp to process lignocellulose materials, the shortcomings of fluff pulp in the face of body fluid odor control are solved, significant ammonia inhibition effect is achieved, and the odor control performance of the product is improved .
Patent Information
- Application Number
- CN202411133072.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-03-21
- Filing Date
- 2018-03-12
- Publication Date
- 2024-12-13
AI Technical Summary
When existing fluff pulp faces odor problems caused by body fluids, especially the ammonia smell in urine, it is difficult to effectively control the odor, affecting the performance of personal care and medical care products.
By adding low amounts of copper ions to the fluff pulp, combining bleached kraft paper fibers and copper salt and iron salt catalysts, lignocellulosic material is processed to form fluff pulp with significant odor control ability.
It significantly improves the inhibitory effect on ammonia formation, reduces the production of gaseous ammonia, improves the odor control properties of fuzzy pulp, and is suitable for applications such as diaper fuzzy and incontinence products.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_6
Abstract
Description
[0001] This patent application is a divisional application of the patent application with application number 201880033138.8 (international application number PCT / US2018 / 021991), applicant is "International Paper Company", and invention name is "Odor Control Pulp Composition". Technical Field
[0002] The present technology generally relates to fluff pulp having improved odor control and methods of making such fluff pulp. Summary of the invention
[0003] In one aspect, a fluff pulp is provided that includes bleached kraft fiber and a copper ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber. The bleached kraft fiber includes a length-weighted average fiber length of at least about 2 mm, a copper value of less than about 7, a carboxyl content of greater than about 3.5 meq / 100 grams; an ISO brightness of at least 80; and a viscosity of about 2 cps to about 9 cps, wherein the fluff pulp has a copper ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
[0004] In a related aspect, a process for preparing fluff pulp is provided. The process comprises treating a lignocellulosic material by adding a catalyst consisting of a combination of copper and iron or their salts in an amount of about 50 ppm to about 200 ppm by weight of the lignocellulosic material in the presence of about 0.5% to about 5% by weight of an oxidant to produce a treated lignocellulosic material. In the process, the weight ratio of iron and iron salts to copper and copper salts is at most about 10:1. The treated lignocellulosic material has a viscosity of about 2 cps to about 6 cps and has an inhibition of ammonia formation of at least 50% greater than a second treated lignocellulosic material formed by the same process in the absence of copper. The lignocellulosic material can be a lignocellulosic kraft pulp, such as a lignocellulosic kraft pulp that has been bleached with chlorine dioxide.
[0005] In any embodiments herein, the process can include treating lignocellulosic kraft pulp by adding about 50 ppm to about 200 ppm of a catalyst by weight of the lignocellulosic kraft pulp in the presence of about 0.5% to about 5% oxidizing agent by weight of the lignocellulosic kraft pulp at an acidic pH to produce a treated lignocellulosic material.
[0006] In any embodiments herein, the process can include treating lignocellulosic kraft pulp to produce a treated lignocellulosic material by adding about 50 ppm to about 150 (or about 200) ppm of a catalyst, by weight of the lignocellulosic kraft pulp, in the presence of about 0.5% to about 5% oxidant, by weight of the lignocellulosic kraft pulp, at a pH of about 2.5 to about 5 to produce a treated lignocellulosic material; wherein the lignocellulosic kraft pulp is in an aqueous solution of about 8 wt % to about 12 wt % lignocellulosic kraft pulp based on water in the solution; the weight ratio of iron and iron salts to copper and copper salts is about 8:1 to about 1:8; and the treated lignocellulosic material has a viscosity of about 3 cps to about 5 cps.
[0007] In another related aspect, a process for improving the odor control properties of fluff pulp is provided. The process comprises treating a first lignocellulosic material to form a second lignocellulosic material by adding from about 3.5 ppm to about 200 ppm of a copper salt and from about 25 ppm to about 175 (or about 196.5) ppm of an iron salt at a pH of from about 1 to about 9, wherein the weight ratio of the iron salt to the copper salt is from about 8:1 to about 1:1; and the dried second lignocellulosic material inhibits ammonia formation by at least 50% greater than the dried first lignocellulosic material. DETAILED DESCRIPTION
[0008] I. Definitions
[0009] The following terms are used throughout, as defined below.
[0010] As used herein and in the appended claims, singular articles such as "a", "an" and "the" and similar references in the context of describing elements (particularly in the context of the following claims) should be interpreted as covering the singular and plural, unless otherwise specified herein or clearly contradictory to the context. The enumeration of numerical ranges herein is intended only to be used as a shorthand method for referring to each individual value falling within the range individually, unless otherwise specified herein, and each individual value is incorporated into the specification as if it were individually narrated herein. All methods described herein can be performed in any suitable order, unless otherwise specified herein or clearly contradictory to the context. The use of any and all examples or exemplary language (e.g., "such as") provided herein is intended only to better illustrate the embodiments and is not intended to limit the scope of the claims, unless otherwise specified. Any language in the specification should not be interpreted as indicating that any unclaimed element is essential.
[0011] As used herein, "about" will be understood by one of ordinary skill in the art and will vary to some extent depending on the context in which it is used. If there is a use of a term that is unclear to one of ordinary skill in the art, "about" will mean plus or minus 10% of the particular term, depending on the context in which it is used.
[0012] As will be understood by those skilled in the art, for any and all purposes, particularly in providing written descriptions, all scopes disclosed herein also encompass any and all possible sub-ranges and combinations of sub-ranges thereof.Any listed range can be easily identified as fully describing and capable of decomposing the same range into at least equal half, one-third, one-quarter, one-fifth, one-tenth, etc. As a non-limiting example, each range discussed herein can be easily decomposed into lower third, middle third, and upper third.As will be understood by those skilled in the art, all languages such as "at most", "at least", "greater than", "less than", etc. include the numbers listed, and refer to the scopes that can be subsequently decomposed into the above-mentioned sub-ranges.Finally, as will be understood by those skilled in the art, scope includes each individual number.Therefore, for example, a group with 1-3 atoms refers to a group with 1, 2 or 3 atoms.Similarly, a group with 1-5 atoms refers to a group with 1, 2, 3, 4 or 5 atoms, and the like.
[0013] As used herein, the term "halide" refers to bromide, chloride, fluoride, or iodide.
[0014] II. This technology
[0015] Cellulose pulp has been used in various personal care or medical care absorbent products, such as diaper fluff or incontinence products. However, odors caused by body fluids are a major problem, such as ammonia from urine in the case of diaper fluff. For other applications, other nitrogen- or sulfur-containing substances may cause odor problems.
[0016] The present technology relates to fluff pulps that exhibit improved odor control and methods of producing such advantageous fluff pulps. The fluff pulps exhibit significantly improved odor control, at least in part, by using surprisingly low amounts of copper. While particularly useful for diaper fluff and incontinence products, the present technology is applicable to any situation where odor control is beneficial and / or advantageous.
[0017] Thus, in one aspect, a fluff pulp is provided that includes bleached kraft fiber and a copper ion content of from about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber. The bleached kraft fiber includes a length-weighted average fiber length of at least about 2 mm, a copper value of less than about 7, a carboxyl content of greater than about 3.5 meq / 100 grams; an ISO brightness of at least 80; and a viscosity of from about 2 cps to about 9 cps. The fluff pulp may or may not include a superabsorbent polymer (SAP), such as sodium polyacrylate polymers and copolymers. The kraft fiber may be derived from softwood fibers, hardwood fibers, or mixtures thereof, wherein such fibers are described in more detail herein.
[0018] As further described herein and in addition to other features of fluff pulp, it was surprisingly found that including a copper ion content of about 0.2 ppm to about 50 ppm by weight of the copper bleached kraft fiber significantly improved odor control properties compared to fluff pulp without copper. In fact, one of ordinary skill in the art would not expect significant odor control properties due to the inclusion of such low copper ion levels.
[0019] The fluff pulp can have at least 50% greater inhibition of ammonia formation than a second fluff pulp having the same characteristics but without copper (i.e., a fluff pulp having the same composition except that copper ions are not included in the fluff pulp). "Inhibition of ammonia formation" means that the fluff pulp has less gaseous ammonia than a fluff pulp having the same composition except that copper ions are not included in the fluff pulp, as determined by testing of Example 1 (absence of SAP) and / or Example 2 (presence of SAP). Without being bound by theory, the inhibition may be due to increased absorption of NH3 in the fluff pulp, prevention of conversion of nitrogen-containing compounds to NH3, or a combination of both. The inhibition can be at least about 50% greater, at least about 55% greater, at least about 60% greater, at least about 65% greater, at least about 70% greater, at least about 75% greater, at least about 80% greater, at least about 85% greater, at least about 90% greater, at least about 92% greater, at least about 94% greater, at least about 96% greater, at least about 98% greater, at least about 99% greater, approximately 100%, or any range including any two of these values and / or any range between any two of these values.
[0020] The copper ions of the copper ion content may be combined with the bleached kraft fiber and / or may be in the form of a copper (I) salt, a copper (II) salt, a hydrate thereof, or a combination of any two or more thereof. Copper (I) salts include, but are not limited to, copper (I) chloride, copper (I) oxide, copper (I) sulfate, or a combination of any two or more thereof. Copper (II) salts include, but are not limited to, copper (II) carbonate, copper (II) chloride, copper (II) phosphate, copper (II) nitrate, copper (II) perchlorate, copper (II) phosphate, copper (II) sulfate, copper (II) tetrafluoroborate, copper (II) trifluoromethanesulfonate, or a combination of any two or more thereof. Non-kraft fiber ligands of copper and / or salts thereof may be included in the fluff pulp, wherein such ligands include, but are not limited to, ethylenediaminetetraacetic acid, (S,S')-ethylenediamine-N,N'-disuccinic acid, diethylenetriaminepentaacetic acid, ethylene glycol-bis(2-aminoethyl)-N,N,N',N'-tetraacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, or mixtures of any two or more thereof. Non-kraft fiber ligands may not be included in the fluff pulp. In contrast to non-kraft fiber ligands, "kraft fiber ligands" are a portion or part of kraft fiber.
[0021] The copper ion content in the fluff pulp determined by the weight of the bleached kraft fiber can be about 0.2ppm, about 0.5ppm, about 1ppm, about 2ppm, about 3ppm, about 4ppm, about 5ppm, about 6ppm, about 7ppm, about 8ppm, about 9ppm, about 10ppm, about 12ppm, about 14ppm, about 16ppm, about 18ppm, about 20ppm, about 22ppm, about 24ppm, about 26ppm, about 28ppm, about 30ppm, about 32ppm, about 34ppm, about 36ppm, about 38ppm, about 40ppm, about 42ppm, about 44ppm, about 46ppm, about 48ppm, about 50ppm, and any range including any two of these values and / or any range between any two of these values. The copper ion content can be determined by conventional analytical methods, such as ICP-atomic absorption. Therefore, the value of the copper ion content refers to Cu +1 ions and / or Cu +2 The mass of the ion itself, rather than the total mass of the copper salt (e.g., the total mass of copper sulfate). As a further example, the mass of the copper ion in copper sulfate is about 0.4 of the total mass of the copper sulfate.
[0022] Fluff pulp may or may not include iron ions. The iron ions associated with bleached kraft fiber may be ferrous salts (Fe 2+ ), ferric iron salt (Fe 3+), hydrates thereof, and combinations of any two or more thereof. Ferrous and / or ferric salts include halides, sulfates, nitrates, phosphates, carbonates, and combinations of any two or more thereof. Examples include, but are not limited to, ferrous sulfate (e.g., ferrous sulfate heptahydrate), ferrous chloride, ammonium ferrous sulfate, ferric chloride, ammonium ferric sulfate, or ammonium ferric citrate. The amount of iron ions in the fluff pulp ("iron ion content") can be from about 0.2 ppm to about 50 ppm based on the weight of the bleached kraft fiber; thus, the amount of iron ions based on the weight of the bleached kraft fiber can be about 0.2 ppm, about 0.5 ppm, about 1 ppm, about 2 ppm, about 3 ppm, about 4 ppm, about 5 ppm, about 6 ppm, about 7 ppm, about 8 ppm, about 9 ppm, about 10 ppm, about 12 ppm, about 14 ppm, about 16 ppm, about 18 ppm, about 20 ppm, about 22 ppm, about 24 ppm, about 26 ppm, about 28 ppm, about 30 ppm, about 32 ppm, about 34 ppm, about 36 ppm, about 38 ppm, about 40 ppm, about 42 ppm, about 44 ppm, about 46 ppm, about 48 ppm, about 50 ppm, or any range including any two of these values and / or any range between any two of these values. The iron content can be determined by conventional analytical methods, such as ICP-atomic absorption.
[0023] As previously described, the bleached kraft fiber has a length weighted average fiber length of at least about 2 mm. The length weighted average fiber length of the bleached kraft fiber can be about 2 mm, about 2.1 mm, about 2.2 mm, about 2.3 mm, about 2.4 mm, about 2.5 mm, about 2.6 mm, about 2.7 mm, about 2.8 mm, about 2.9 mm, about 3.0 mm, about 3.1 mm, about 3.2 mm, about 3.3 mm, about 3.4 mm, about 3.5 mm, about 3.6 mm, about 3.7 mm, about 3.8 mm, about 3.9 mm, about 4.0 mm, or any other range greater than any of these values, or any range including any two of these values and / or any range between any two of these values. Such length weighted average fiber length can be measured by a Fiber Quality Analyzer available from OPTEST, Hawkesbury, Ontario, according to the manufacturer's standard procedure. TM to be sure.
[0024] Bleached kraft fiber has a copper value of less than about 7. The copper value can be measured according to TAPPI T430-cm99. The copper value of bleached kraft fiber can be about 1, about 2, about 3, about 4, about 5, about 6, about 7, or any range less than any one of these values, or any range including any two of these values and / or any range between any two of these values. Bleached kraft fiber also has a carboxyl content greater than about 3.5 meq / 100 grams, wherein the carboxyl content can be measured according to TAPPI T237-cm98. Therefore, the carboxyl content (in meq / 100 grams) of bleached kraft fiber can be about 3.6, about 3.8, about 4.0, about 4.5, about 5, about 5.5, about 6, about 6.5, about 7, about 7.5, about 8, or any range including any two of these values and / or any range between any two of these values. The carboxyl content can be measured according to TAPPI T237-cm98.
[0025] The bleached kraft fiber of the fluff pulp has an ISO brightness of at least 80. The ISO brightness can be determined according to TAPPIT525-om02. The ISO brightness of the bleached kraft fiber can be 80, about 82, about 84, about 86, about 88, about 90, about 91, about 92, about 93, about 94, about 95, or any range including any two of these values and / or any range between any two of these values. In any embodiment of the present invention, the bleached kraft fiber may not include a fluorescent whitening agent. In any embodiment of the present invention, the fluff pulp may not include a fluorescent whitening agent.
[0026] As previously described herein, the bleached kraft fiber of the fluff pulp has a viscosity of about 2 cps to about 9 cps. The viscosity of the bleached kraft fiber can be determined according to the procedure of TAPPI T230-om99. Thus, the viscosity of the bleached kraft fiber can be about 2, about 2.5, about 3, about 3.5, about 4, about 4.5, about 5, about 5.5, about 6, about 6.5, about 7, about 7.5, about 8, about 8.5, about 9, or any range including any two of these values and / or any range between any two of these values.
[0027] In a related aspect, a process for preparing fluff pulp is provided. The process comprises treating a lignocellulosic material by adding from about 50 ppm to about 200 ppm, by weight of the lignocellulosic material, of a catalyst consisting of a combination of copper and / or its salts and iron and / or its salts in the presence of from about 0.5% to about 5% oxidant, by weight of the lignocellulosic material, to produce a treated lignocellulosic material. In the process, the weight ratio of iron and iron salts to copper and copper salts is at most about 10:1. The treated lignocellulosic material has a viscosity of from about 2 cps to about 6 cps and inhibits ammonia formation by at least 50% greater than a second treated lignocellulosic material formed by the same process in the absence of copper. The inhibition can be at least about 50% greater, at least about 55% greater, at least about 60% greater, at least about 65% greater, at least about 70% greater, at least about 75% greater, at least about 80% greater, at least about 85% greater, at least about 90% greater, at least about 92% greater, at least about 94% greater, at least about 96% greater, at least about 98% greater, at least about 99% greater, approximately 100%, or any range including any two of these values and / or any range between any two of these values.
[0028] Lignocellulosic materials can be preferably wood pulp.Lignocellulosic materials can be in fiber and / or particle form, such as pulp fibers, fine powders and / or other pulp fragments, hemicellulose, starch, and / or polysaccharide particles and powders.Lignocellulosic materials can also include cellulose derivatives, such as carboxymethyl cellulose, hydroxypropyl cellulose, etc.Useful lignocellulosic materials include, but are not limited to, those derived from known sources of such materials, such as plants.The example of useful lignocellulosic materials is polysaccharides, such as starch, as described in U.S. Patent No. 8,007,635, which is incorporated herein by reference.The exemplary lignocellulosic materials used in the process described in any embodiment herein are pulp fibers, which are used to form paper towels, towels, diapers, feminine hygiene and adult incontinence products, and for making other types of pulp products, paper and / or paperboard.Such pulp fibers include those derived from hardwood trees, softwood trees, or a combination of hardwood and softwood trees prepared for use in papermaking equipment by any known suitable digestion, refining and / or bleaching operations (e.g., known mechanical, thermomechanical, chemical and semichemical, etc., pulping and other pulping methods known to those of ordinary skill in the art). As used herein, the term "hardwood pulp" refers to fiber pulp derived from woody matter of deciduous trees (angiosperms), while "softwood pulp" refers to fiber pulp derived from woody matter of coniferous trees (gymnosperms). Useful pulp fibers can be provided from non-woody herbaceous plants, including but not limited to kenaf, jute, flax, sisal and / or abaca. Bleached or unbleached pulp fibers, such as unbleached kraft pulp and bleached kraft pulp (collectively referred to as "lignocellulosic kraft pulp"), and / or recycled pulp, can be used in any embodiment of the process described herein. The pulp may have undergone any treatment history normal in pulping and bleaching, or may be intentionally modified, such as controlled prehydrolysis and / or alkaline extraction of chips before kraft pulping, acid and / or enzyme (e.g., cellulase and / or hemicellulase) hydrolysis of kraft pulp, and / or "cold soda" treatment of pulp (to achieve mercerized strength).
[0029] "Copper and / or its salts" refers to elemental copper (Cu 0), copper (I) salts, copper (II) salts, hydrates thereof, or any combination of two or more thereof. Copper (I) salts include but are not limited to copper (I) chloride, copper (I) oxide, copper (I) sulfate, or any combination of two or more thereof, and copper (II) salts include but are not limited to copper (II) carbonate, copper (II) chloride, copper (II) phosphate, copper (II) nitrate, copper (II) perchlorate, copper (II) phosphate, copper (II) sulfate, copper (II) tetrafluoroborate, copper (II) trifluoromethanesulfonate, or any combination of two or more thereof. In any embodiments herein, copper and / or its salts can be added in an amount of about 3.5 ppm to about 199.8 ppm based on the weight of the lignocellulosic material; thus, copper or its salts can be added in an amount of about 3.5 ppm, about 4 ppm, about 4.5 ppm, about 5 ppm, about 5.5 ppm, about 6 ppm, about 7 ppm, about 8 ppm, about 9 ppm, about 10 ppm, about 12 ppm, about 14 ppm, about 16 ppm, about 18 ppm, about 20 ppm, about 22 ppm, about 24 ppm, about 26 ppm, about 28 ppm, about 30 ppm, about 32 ppm, about 34 ppm, about 35 ppm, about 36 ppm, about 37 ppm, about 38 ppm, about 39 ppm, about 40 ppm, about 41 ppm, about 42 ppm, about 43 ppm, about 44 ppm, about 45 ppm, about 46 ppm, about 47 ppm, about 48 ppm, about 49 ppm, about 50 ppm, about 51 ppm, about 52 ppm, about 53 ppm, about 54 ppm, about 55 ppm, about 56 ppm, about 57 ppm, about 58 ppm, about 59 ppm, about 60 ppm, about 61 ppm, about 62 ppm, about 63 ppm, about 64 ppm, about 65 ppm, about 66 ppm, about 67 ppm, about 68 ppm, about 69 ppm, about 70 ppm, about 71 ppm, about 72 ppm, about 73 ppm, about 74 ppm, about 75 6ppm, about 38ppm, about 40ppm, about 42ppm, about 44ppm, about 46ppm, about 48ppm, about 50ppm, about 55ppm, about 60ppm, about 65ppm, about 70ppm, about 75ppm, about 80ppm, about 85ppm, about 90ppm, about 95ppm, about 100ppm, about 120ppm, about 140ppm, about 160ppm, about 180ppm, about 190ppm, about 199.8ppm, about 200ppm, or any range including any two of these values and / or any range between any two of these values.
[0030] "Iron and / or its salts" refers to elemental iron (Fe 0 ), ferrous iron (Fe 2+ ) salt, ferric iron (Fe 3+) salt, its hydrate, and any two or more combinations thereof. Preferred salts of ferrous salts and / or ferric salts include halides, sulfates, nitrates, phosphates, carbonates, and any two or more combinations thereof. Examples include, but are not limited to, ferrous sulfate (e.g., ferrous sulfate heptahydrate), ferrous chloride, ammonium ferrous sulfate, ferric chloride, ammonium ferric sulfate, or ammonium ferric citrate. In any embodiment herein, the addition amount of iron or its salt can be about 0.2ppm to about 180ppm by weight of the lignocellulosic material; therefore, the addition amount of iron or its salt can be about 0.2ppm, about 0.5ppm, about 1ppm, about 2ppm, about 3ppm, about 4ppm, about 5ppm, about 6ppm, about 7ppm, about 8ppm, about 9ppm, about 10ppm, about 12ppm, about 14ppm, about 16ppm, about 18ppm, about 20ppm about 22ppm, about 24ppm, about 26ppm, about 28ppm, about 30ppm, About 32ppm, about 34ppm, about 36ppm, about 38ppm, about 40ppm, about 42ppm, about 44ppm, about 46ppm, about 48ppm, about 50ppm, about 55ppm, about 60ppm, about 65ppm, about 70ppm, about 75ppm, about 80ppm, about 85ppm, about 90ppm, about 95ppm, about 100ppm, about 120ppm, about 140ppm, about 160ppm, about 180ppm, or any range including any two of these values and / or any range between any two of these values.
[0031] In this process, the weight ratio of iron and iron salt to copper and copper salt is up to about 10: 1. The phrase "up to about 10: 1" means not including a greater ratio of iron and iron salt to copper and copper salt, such as 11: 1, but does not include a range that does not include iron because there is no ratio at all. The weight ratio of iron and iron salt to copper and copper salt can be about 10: 1, about 9: 1, about 8: 1, about 7: 1, about 6: 1, about 5: 1, about 4: 1, about 3: 1, about 2: 1, about 1: 1, about 1: 2, about 1: 3, about 1: 4, about 1: 5, about 1: 6, about 1: 7, about 1: 8, about 1: 9, about 1: 10, or any range including any two of these values and / or any range between any two of these values.
[0032] The oxidant may include one or more of hydrogen peroxide, chlorine dioxide, hypochlorite and hypochlorous acid. Preferred oxidants include hydrogen peroxide. The amount of the oxidant is about 0.5% to about 5% oxidant by weight of the lignocellulosic material. Therefore, the amount of the oxidant may be about 0.5%, about 0.6%, about 0.7%, about 0.8%, about 0.9%, about 1%, about 1.2%, about 1.4%, about 1.6%, about 1.8%, about 2%, about 2.2%, about 2.4%, about 2.6%, about 2.8%, about 3%, about 3.2%, about 3.4%, about 3.6%, about 3.8%, about 4%, about 4.2%, about 4.4%, about 4.6%, about 4.8%, about 5%, or any range including any two of these values and / or any range between any two of these values.
[0033] Catalyst can be added under the existence of the oxidant by weight of lignocellulosic material at a pH value of about 1 to about 9.Processing pH value can vary widely, and can use any temperature that is enough to form required treated lignocellulosic material.Processing pH can be about 1.0, about 1.5, about 2.0, about 2.5, about 3.0, about 3.5, about 4.0, about 4.5, about 5.0, about 5.5, about 6.0, about 6.5, about 7.0, about 7.5, about 8.0, about 8.5, about 9.0 or comprise any scope of any two of these values and / or any scope between any two of these values.For example, pH can be acidic pH (that is, about 1 to less than about 7), and pH can be preferably about 2 to about 6, and more preferably about 2.5 to about 5.
[0034] When the amount of another component is determined based on the weight of, for example, a lignocellulosic material, it is based on the dry weight of the lignocellulosic material. A lignocellulosic material (e.g., a lignocellulose kraft pulp) can be in an aqueous solution of a lignocellulosic material of about 8wt% to about 16wt% based on the water in the solution. Therefore, the lignocellulosic material can be in an aqueous solution of about 8wt%, about 9wt%, about 10wt%, about 11wt%, about 12wt%, about 13wt%, about 14wt%, about 15wt%, about 16wt%, or any range including these values and / or any range between these values.
[0035] The treatment temperature can vary widely, and any temperature that is enough to form the desired treated lignocellulose product can be used. The treatment temperature is generally at least about 20°C, but lower temperatures can also be used if the desired lignocellulose material is effectively provided. The treatment temperature can be about 20°C, about 40°C, about 50°C, about 60°C, about 65°C, about 70°C, about 75°C, about 80°C, about 85°C, about 90°C, about 95°C, about 100°C, about 110°C, about 120°C, or any range including any two of these values and / or any range between any two of these values. The treatment temperature is preferably about 40°C to about 120°C, more preferably about 40°C to about 90°C, and most preferably about 65°C to about 90°C.
[0036] The treatment time can vary widely, and can use any time that is enough to form required treated lignocellulose product.The treatment time is generally at least about 5 minutes, but can use longer treatment time if required lignocellulose material is provided effectively.The treatment time is preferably about 5 minutes to about 20 hours, more preferably about 15 minutes to about 10 hours, more preferably about 30 minutes to about 4 hours.Suitable treatment time comprises about 5 minutes, about 10 minutes, about 30 minutes, about 1 hour, about one and a half hours, about 2 hours, about 3 hours, about 4 hours, about 6 hours, about 8 hours, about 10 hours, about 15 hours, about 20 hours or comprises any two any scopes in these values and / or any scope between any two in these values.
[0037] Alternatively, in addition to catalyst and oxidant, with or without UV radiation, it is preferred to perform the process when hydrogen peroxide is used as an oxidant. The advantage of including UV radiation is that it is more effective at lower temperatures (e.g., room temperature (or ambient temperature)), without the need for heating equipment, and can be used to expand the pH effective range. For example, the process can be effectively performed in the presence of UV radiation at ambient temperature (or without heating), at approximately neutral pH (i.e., from about 6.8 to about 7.2), and / or for example, depending on the power of the UV lamp in a very short time from a few seconds to about 1 hour. The UV lamp used in the process is preferably a high-intensity lamp, such as a medium-pressure mercury arc lamp or its variant, a pulsed xenon flash lamp, or an excimer lamp. It is most preferred to use a medium-pressure mercury arc lamp, which is low in cost and easily available from commercial sources. One or more UV lamps that are usually inserted into a quartz sleeve can be inserted into (immersed in) pulp for irradiation. Sometimes, it may be more advantageous to place a UV lamp above a mixed suspension of lignocellulosic material. For this type of UV irradiation, a mercury arc lamp and an electrodeless power supply lamp (e.g., from Fusion UV Company) can be used. It is preferred that the pulp be well mixed and stirred during the reaction because the UV penetration rate in water is very low and most of the chemical action is caused by UV decomposition of peroxides in aqueous solution. In any embodiment herein, the UV treatment can be performed with or without the addition of a UV catalyst. Useful UV catalysts include, but are not limited to, micron or nanoparticle titanium dioxide or zinc oxide photocatalysts; azo-based water-soluble organic catalysts, such as 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylpropylamidine) dihydrochloride, 2,2'-azobis(2-methylpropionitrile) (AIBN), 1,1'-azobiscyclohexanecarbonitrile (e.g., DuPont Catalyst 88), and / or (2,2,6,6-tetramethylpiperidinyl)oxy (TEMPO).
[0038] The process can be carried out in batches, continuously or semi-continuously. The process can also be implemented as a process step at the end of a mechanical, semi-chemical or chemical pulping process as part of a pulping process, or as a step at the end of a bleaching process as part of a multi-step bleaching process (i.e., no further bleaching step is performed after the treatment step of the process). The process can also be used to treat commercial paper pulp and / or fluff pulp, for example by re-rinsing commercial paper pulp or fluff pulp in a hydraulic pulper or similar device. The treatment in a hydraulic pulper or similar device has the flexibility of adjusting conditions. For example, the treatment can be started at an acidic pH, and after some suitable time periods, the treatment includes adjusting to an alkaline pH by adding caustic soda, and continuing the reaction at a higher pH. The combined acid-alkaline treatment can be used to change the ratio of carboxyl to carbonyl in the treated lignocellulosic material.
[0039] The treated lignocellulosic material can have any one or more of the characteristics previously described for fluff pulp (e.g., a length-weighted average fiber length of at least about 2 mm, a copper value of less than about 7, a carboxyl content of greater than about 3.5 meq / 100 grams; an ISO brightness of at least 80; and a viscosity of about 2 cps to about 9 cps, or a combination of any two or more thereof) and any ranges described herein. In any embodiments herein, and as previously discussed for fluff pulp, the treated lignocellulosic material can have a copper ion content of about 0.2 ppm to about 50 ppm, based on the weight of the treated lignocellulosic material, or any range of copper ion content described herein. In any embodiments herein, and as previously discussed for fluff pulp, the treated lignocellulosic material can have an iron ion content of about 0.2 ppm to about 50 ppm, based on the weight of the treated lignocellulosic material.
[0040] In another related aspect, a process for improving the odor control properties of fluff pulp is provided, wherein the process comprises treating a first lignocellulosic material to form a second lignocellulosic material by adding from about 0.5 ppm to about 200 ppm of a copper salt at a pH of from about 1 to about 9, wherein the dried second lignocellulosic material inhibits ammonia formation by at least 50% greater than the dried first lignocellulosic material. The inhibition may be at least about 50% greater, at least about 55% greater, at least about 60% greater, at least about 65% greater, at least about 70% greater, at least about 75% greater, at least about 80% greater, at least about 85% greater, at least about 90% greater, at least about 92% greater, at least about 94% greater, at least about 96% greater, at least about 98% greater, at least about 99% greater, about 100%, or any range including any two of these values and / or any range between any two of these values. The pH can be about 1.0, about 1.5, about 2.0, about 2.5, about 3.0, about 3.5, about 4.0, about 4.5, about 5.0, about 5.5, about 6.0, about 6.5, about 7.0, about 7.5, about 8.0, about 8.5, about 9.0, or any range including and / or between any two of these values.
[0041] In any embodiment of this process herein, the first lignocellulosic material may not contain more than about 0.2 ppm copper, and preferably no more than about 0.1 ppm copper, more preferably no more than about 0.01 ppm copper. In any embodiment herein, the first lignocellulosic material may not contain detectable copper measured by ICP-atomic absorption.
[0042] Copper salts are described above, and the term "copper salt" means a copper salt, a mixture of any two or more copper salts, a hydrate of any one or more of the foregoing, and a combination of any two or more thereof, wherein the copper salt may be added in an amount of about 0.5 ppm, about 0.6 ppm, about 0.7 ppm, about 0.8 ppm, about 0.9 ppm, about 1.0 ppm, about 1.2 ppm, about 1.4 ppm, about 1.6 ppm, about 1.8 ppm, about 2.0 ppm, about 2.5 ppm, about 3.5 ppm, about 4 ppm, about 4.5 ppm, about 5 ppm, about 5.5 ppm, about 6 ppm, about 7 ppm, about 8 ppm, about 9 ppm, about 10 ppm, about 12 ppm, about 14 ppm, about 16 ppm, about 18 ppm, about 20 ppm ppm, about 199.8 ppm, about 200 ppm, or any range including any two of these values and / or any range between any two of these values.
[0043] Lignocellulosic materials are also described above. In this process, the lignocellulosic material is preferably bleached kraft pulp, more preferably a fluff pulp comprising bleached kraft fibers. The bleached kraft fibers / pulp can have any one or more of the characteristics described for the bleached kraft fibers of the fluff pulp of the present technology (e.g., a length-weighted average fiber length of at least about 2 mm, a copper value of less than about 7, a carboxyl content of greater than about 3.5 meq / 100 grams, an ISO brightness of at least 80, a viscosity of about 2 cps to about 9 cps, or a combination of any two or more thereof) and any ranges described herein.
[0044] It is also possible to add an iron salt together with a copper salt, such as about 25 ppm to about 175 ppm of an iron salt. Iron salts are described above, wherein the term "iron salt" means an iron salt, a mixture of any two or more iron salts, a hydrate of any one or more of the foregoing, and any combination of two or more thereof. The addition amount of iron salt can be about 25ppm, about 26ppm, about 28ppm, about 30ppm, about 32ppm, about 34ppm, about 36ppm, about 38ppm, about 40ppm, about 42ppm, about 44ppm, about 46ppm, about 48ppm, about 50ppm, about 55ppm, about 60ppm, about 65ppm, about 70ppm, about 75ppm, about 80ppm, about 85ppm, about 90ppm, about 95ppm, about 100ppm, about 120ppm, about 140ppm, about 160ppm, about 165ppm, about 170ppm, about 175ppm, or any range including any two of these values and / or any range between any two of these values. In this process, the weight ratio of iron salt to copper salt is at most about 10: 1. The phrase "at most about 10: 1" means not including a larger ratio of iron salt to copper salt, such as 11: 1, but does not include a range that does not include iron because there is no ratio at all. The weight ratio of the iron salt to the copper salt can be about 10:1, about 9:1, about 8:1, about 7:1, about 6:1, about 5:1, about 4:1, about 3:1, about 2:1, about 1:1, about 1:2, about 1:3, about 1:4, about 1:5, about 1:6, about 1:7, about 1:8, about 1:9, about 1:10, or any range including and / or between any two of these values.
[0045] For example, the process can include treating a first lignocellulosic material by adding about 3.5 ppm to about 200 ppm of a copper salt and about 25 ppm to about 175 ppm of an iron salt at a pH of about 1 to about 9 to form a second lignocellulosic material.
[0046] In any embodiment herein, copper salt (and, when applicable, iron salt) can be added as an aqueous solution. In such an embodiment, the process can include treating the first lignocellulosic material to provide a wet lignocellulosic material by adding an aqueous solution of copper salt (and, if applicable, iron salt) at a pH of about 1 to about 9; and drying the wet lignocellulosic material to form a second lignocellulosic material, wherein the second lignocellulosic material includes about 0.5ppm to about 200ppm of copper salt (or any previously described range), and when including iron salt, includes about 25ppm to about 175ppm of iron salt (or any previously described range). The process can also include drying the wet lignocellulosic material, and then fiberizing to form a second lignocellulosic material.
[0047] In any embodiments herein, the second lignocellulosic material can have any one or more of the characteristics previously described for fluff pulp (e.g., a length-weighted average fiber length of at least about 2 mm, a copper value of less than about 7, a carboxyl content of greater than about 3.5 meq / 100 grams; an ISO brightness of at least 80; and a viscosity of about 2 cps to about 9 cps, or a combination of any two or more thereof) and any ranges described herein. In any embodiments herein, and as previously discussed for fluff pulp, the treated lignocellulosic material can have a copper ion content of about 0.2 ppm to about 50 ppm, based on the weight of the treated lignocellulosic material, or any range of copper ion content described herein. In any embodiments herein, and as previously discussed for fluff pulp, the treated lignocellulosic material can have an iron ion content of about 0.2 ppm to about 50 ppm, based on the weight of the treated lignocellulosic material.
[0048] The treated lignocellulosic material or the second lignocellulosic material can be subjected to a number of subsequent treatments to further modify the properties of the material. For example, in any embodiment herein, the treated lignocellulosic material or the second lignocellulosic material can be treated with a cationic agent, which (without being bound by theory) is believed to bind the reducing functional groups of the treated material. Useful cationic materials can vary over a wide range, including but not limited to cationic nitrogen-containing polymers, such as polyamines, 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (EDC), hexadimethylbromethane, polyethyleneimine (linear and / or branched), copolymers of diallyldimethylammonium chloride (DADMAC), copolymers of vinyl pyrrolidone (VP) and quaternized diethylaminoethyl methacrylate (DEAMEMA), polyamides, cationic polyurethane latexes, cationic polyvinyl alcohols, polyalkylamines, dicyandiamide copolymers , amine glycidyl addition polymers, poly[oxyethylene(dimethylimino)ethylene(dimethylimino)ethylene]dichloride, high charge density polyethyleneamine, polyallylamine (PAH), poly(hexamethylene biguanide hydrochloride) (PHMB), polyamidoamine (or polyethyleneimine); cationic metal ions, such as water-soluble aluminum salts, calcium salts and / or zirconium salts; and cationic dendrimers, such as (polyamidoamine) dendrimers with amino surface groups (PAMAM dendrimers), and polypropyleneimine dendrimers with amino surface groups. Without being bound by theory, it is believed that treatment with such cationic materials can modify properties, such as increasing paper bulk, which is ideal for fine paper, paperboard, tissue, towels and absorbent products, while maintaining good strength and having a reduced water retention value (WRV) and increased freeness.
[0049] The treated lignocellulosic material or the second lignocellulosic material can be treated with micron or nanoparticle metal oxides, such as aluminum oxide, titanium oxide, zinc oxide and / or silicon dioxide, wherein such materials are retained by the treated lignocellulosic material to modify properties, such as colorant fixation, dye fixation, optical brightener fixation, printability and / or odor control properties. The treated lignocellulosic material or the second lignocellulosic material can be treated with a cross-linking material during papermaking or web formation. Exemplary crosslinking materials include water-dispersible or water-soluble di- or multifunctional carbodiimides and / or polycarbodiimides, such as 1,6-hexamethylenebis(ethylcarbodiimide); 1,8-octamethylenebis(ethylcarbodiimide); 1,10-decamethylbis(ethylcarbodiimide); 1,12-dodecylbis(ethylcarbodiimide); PEG-bis(propyl(ethylcarbodiimide); 2,2'-dithioethylbis(ethylcarbodiimide); 1,1'-dithio-p-phenylenebis(ethylcarbodiimide); and 1,1'-dithio-m-phenylenebis(ethylcarbodiimide). The di- or multifunctional carbodiimide groups react with the reducing functional groups of the treated lignocellulosic material (or the second lignocellulosic material) and crosslink with the fibers of the material within the paper or web structure.
[0050] The treated lignocellulosic material or the second lignocellulosic material can be used for conventional purposes in situ, or for conventional purposes after separation using conventional product separation techniques. For example, the treated lignocellulosic material or the second lignocellulosic material can be used to make a paper or paperboard substrate or web. Methods and devices for preparing a substrate formed of lignocellulosic fibers are well known in the field of paper and paperboard. See, for example, "Handbook For Pulp & Paper Technologies" Second Edition, GASmook, Angus Wilde Publishers (1992), and references cited therein. Any conventional method and apparatus can be used. Preferably, this process using the treated lignocellulosic material (or the second lignocellulosic material) includes: a) depositing an aqueous suspension of lignocellulosic fibers from the treated lignocellulosic material on a forming wire of a paper machine to form a wet paper or paperboard web; b) drying the wet paper or paperboard web to obtain a dry paper or paperboard web, and c) calendering the dried paper or paperboard web. In addition to these, additional steps known to those skilled in the art may be employed; for example, a coating step of coating one or more surfaces of the dried paper or paperboard web with a coating comprising dispersed pigments containing a binder, and / or treating the dried paper or paperboard with a sizing agent such as starch at a size press.
[0051] The treated lignocellulosic material or the second lignocellulosic material can be used to prepare absorbent articles, such as diapers, tissues, towels and / or personal hygiene products using conventional processes. Such products and methods of making them are known to those of ordinary skill in the art. See, for example, U.S. Patents Nos. 6,063,982 and 5,766,159 (incorporated herein by reference except for any portion that may conflict with the present teachings), and the references described therein. Treated lignocellulosic kraft pulp (which must include treated kraft pulp fibers) can be used to make saturated kraft paper. Saturated kraft paper is a paper sheet made from unbleached kraft pulp (usually a mixture of most hardwoods and some softwoods (e.g., southern pine)) that is used as a substrate for impregnation and curing with a resin polymer. Saturated kraft paper is used as a home and office building material, such as a kitchen countertop. The useful property of saturated kraft paper is to control the rate at which a liquid (usually a polymer resin solution) penetrates the sheet while maintaining the paper porosity and density. All of the hardwood kraft fibers in the saturated sheet can be replaced with softwood, such as southern pine kraft (paperboard grade pine kraft) treated by the process of any of the embodiments herein to provide a saturated kraft with good liquid transport properties.
[0052] Example
[0053] The examples herein are provided to illustrate the advantages of the present technology, and further help those of ordinary skill in the art to prepare or use the process of the present technology. In order to more fully illustrate the preferred aspects of the present technology, the examples herein are also given. The embodiments should never be interpreted as limiting the scope of the present technology. The examples may include or contain any variation, embodiment or aspect of the above-mentioned present technology. The above-mentioned variation, embodiment or aspect may also further include or contain any or all other variations, embodiments or aspect variations of the present technology.
[0054] Example 1. Technique for measuring ammonia inhibition properties of fluff pulp in the absence of SAP.
[0055] Sheets of fluff pulp were cut into 2-inch strips and fiberized using a Kamas H01 laboratory hammer mill. The fiberized pulp was made into airlaid pads with a diameter of 50 mm using an airlaid pad former. Each pad was made of 4 grams of fiberized pulp, unless otherwise stated. The pads were compressed to a density of about 0.15 g / cc in a carving press. Two compressed pads were placed in a sealed 1 liter bottle. 40 mL of a 1.0% urease solution (urease from Canavalia ensiformis (Jack Bean), purchased from Sigma) in freshly prepared synthetic urine (RICCA Chemical Company) was added to each 4 gram pad and the bottle was sealed. After 8 hours, the ammonia concentration in the head space of the bottle was detected using a Draeger tube. As provided by the procedure, the lower the concentration of ammonia, the better the ammonia inhibition effect of the fiberized fluff pulp.
[0056] Example 2. Technique for measuring ammonia inhibition properties of fluff pulp using SAP.
[0057] Sheets of fluff pulp were cut into 2 inch strips and fiberized using a Kamas H01 laboratory hammer mill. The fiberized pulp was mixed with SAP to a total weight of 10 grams. For example, if a 10% SAP mat was desired, 9 grams of fiberized pulp was mixed with 1 gram of SAP. The SAP used was (BASF), unless otherwise stated. The mixture of fiberized pulp and SAP was then fed into an airlaid mat former to form a 100 cm 2 A circular pad of 1.5 g / cc was prepared. The pad was compressed to about 0.15 g / cc using a carving press. The pad was placed in a 7 liter sealed container. 100 ml of 1.0% urease solution (described in Example 1) was added to the pad and the container was sealed. After 8 hours, the ammonia concentration in the head space of the container was measured using a Draeger tube.
[0058] Example 3.
[0059] DOE of pulp on an industrial scale op The pulp was collected after the first chlorine dioxide whitening (D1) stage in the D1D2 bleaching sequence and had a viscosity of 16.5 cps. The pulp was treated in acid bleaching stages containing different types and amounts of metal salts as shown in Table 1. Each treatment used 100 grams of dry pulp with a consistency of 10% (i.e., 10 wt% of pulp in solution) and 3% hydrogen peroxide (i.e., 3 wt% based on pulp) at a temperature of 85°C for a period of 130 minutes.
[0060] After treatment, the pulp was washed with 4 L of deionized water and thickened to a solid content of about 20%. The thickened pulp was then diluted with deionized water to a consistency of about 1% and formed into 750 gsm handsheets on an 8 inch by 8 inch handsheet mold. The wet pulp sheet was pressed between blotting papers to remove excess liquid and then dried on a rotary drum dryer at 250°F. The ammonia inhibition properties of the dry sheet were then explored with and without SAP as described in Examples 1 and 2. As shown in Table 1, the use of as little as 25 ppm of CuSO4 in combination with FeSO4 had a significant inhibitory effect on ammonia formation: compared to entry 1, when 25 ppm of CuSO4 was used in acid peroxide bleaching, the ammonia inhibition without SAP was about 50% (100%-(3 ppmNH3 / 6 ppmNH3X100%)=50%). Furthermore, when 50 ppm of CuSO4 was used in combination with 55 ppm of FeSO4, the ammonia suppression was 100% when no SAP was included, and about 82% when 10% SAP was included.
[0061] Table 1.
[0062]
[0063] Example 4.
[0064] Commercial production conditions were performed at the International Paper Riegelwood paper mill in North Carolina. The mill used DOE op The D1D2 bleaching sequence bleached kraft softwood pulp. The D2 stage was changed to produce a low viscosity pulp using 3% hydrogen peroxide and metal salts, wherein the composition and content of the metal salts were varied. The first pulp was produced using 150 ppm FeSO4 as the only metal salt (entry 1, Table 2). The second pulp was produced using 125 ppm FeSO4 and 25 ppm CuSO4 (entry 2, Table 2). Both reaction conditions resulted in a low viscosity pulp.
[0065] Each pulp was then made into fluff pulp sheets on a Fourdrinier paper machine with a cylindrical steam heated can dryer. Samples of each dried sheet were then collected and tested for ammonia inhibition as described in Examples 1 and 2. As shown in Table 2, as little as 25 ppm of CuSO4 used in the acidic hydrogen peroxide bleaching stage had a significant inhibitory effect on ammonia formation. This result was found for pads made with and without SAP.
[0066] Table 2.
[0067]
[0068] Example 5.
[0069] The fluff pulp sheet (RW Plus; commercially produced by International Paper) was soaked in a room temperature (72°F) deionized water bath for one minute with increasing concentrations of copper (II) sulfate pentahydrate (CuSO4.5H2O). After the soaking procedure, the pulp sheets were pressed between blotting papers to remove excess liquid and the sheets were dried on a rotary drum dryer at 250°F. The dried sheets were then tested for ammonia inhibition as described in Examples 1 and 2, with the results of these tests shown in Table 3. As low as 1.0 ppm Cu 2+ It has a significant inhibitory effect on ammonia formation.
[0070] Table 3.
[0071]
[0072]
[0073] Example 6.
[0074] The fluff pulp sheet (RW Plus; commercially produced by International Paper) was sprayed with different aqueous solutions containing deionized water and different concentrations of copper (II) sulfate pentahydrate (CuSO4·5H2O). The fluff pulp sheets were sprayed until they were visibly wet. After the spraying procedure, each pulp sheet was pressed between blotting papers to remove excess liquid and the sheets were dried on a rotary drum dryer at 250°F. Each dried sheet was then tested for ammonia inhibition as described in Example 1, with the results of these tests shown in Table 4. As low as 0.7 ppm Cu 2+ It has a significant inhibitory effect on ammonia formation.
[0075] Table 4.
[0076]
[0077] The present technology is not limited by the specific examples described herein, which are intended to be separate illustrations of various aspects of the present technology. As will be apparent to those skilled in the art, many modifications and changes can be made to the present technology without departing from the spirit and scope of the present invention. According to the foregoing description, in addition to the methods listed herein, functionally equivalent methods within the scope of the present technology are apparent to those skilled in the art. Such modifications and changes are intended to fall within the scope of the appended claims. It should be understood that the present technology is not limited to specific methods, reagents, compounds, compositions or labeled compounds, which can certainly vary. It should also be understood that the terms used herein are only for the purpose of describing specific aspects, and are not intended to be limited.
[0078] The embodiments illustratively described herein may be appropriately implemented in the absence of any one or more elements, one or more limitations not specifically disclosed herein. Thus, for example, the terms "comprises," "comprising," "containing," and the like should be read broadly and without restriction. In addition, the terms and expressions employed herein have been used as terms of description rather than limitation, and it is not intended that such terms and expressions be used to exclude any equivalents of the features shown and described or portions thereof, but it should be recognized that various modifications may be made within the scope of the claimed technology. In addition, the phrase "consisting essentially of..." will be understood to include those elements specifically enumerated and those additional elements that do not materially affect the basic and novel characteristics of the claimed technology. The phrase "consisting of..." excludes any elements that are not specified.
[0079] In addition, where features or aspects of the disclosure are described in terms of Markush groups, those skilled in the art will recognize that the disclosure is also thereby described in terms of any individual member or subgroup of members of the Markush group. Each narrower species and subgeneric grouping falling within the generic disclosure also forms part of the invention. This includes the generic description of the invention with the proviso or negative limitation removing any subject matter from the genus, whether or not the excised material is specifically recited herein.
[0080] All publications, patent applications, issued patents, and other documents (e.g., journals, articles, and / or textbooks) cited in this specification are incorporated herein by reference as if each individual publication, patent application, issued patent, or other document was specifically and individually indicated to be incorporated by reference in its entirety. Definitions contained in the text incorporated by reference are excluded to the extent they conflict with definitions in this disclosure.
[0081] Other embodiments are set forth in the following claims, along with the full scope of equivalents to which such claims are entitled.
Claims
1. A fluff pulp, comprising: Bleached kraft fiber, the bleached kraft fiber comprising: a length-weighted average fiber length of at least about 2 mm; a copper value of less than about 7; and An ISO level of at least 80; and The copper ion content is from about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
2. The fluff pulp according to claim 1, wherein the copper ion of the copper ion content comprises a copper (I) salt, a copper (II) salt, a hydrate thereof, or a combination of any two or more thereof.
3. The fluff pulp according to claim 1, wherein the copper ion content comprises one or more of the following: elemental copper, copper (I) chloride, copper (I) oxide, copper (I) sulfate, copper (II) carbonate, copper (II) chloride, copper (II) phosphate, copper (II) nitrate, copper (II) perchlorate, copper (II) phosphate, copper (II) sulfate, copper (II) tetrafluoroborate and copper (II) trifluoromethanesulfonate.
4. The fluff pulp of claim 1, wherein the fluff pulp further comprises iron ions.
5. The fluff pulp of claim 4, wherein the fluff pulp comprises an iron ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
6. The fluff pulp of claim 1, wherein the fluff pulp does not include super absorbent polymer (SAP).
7. The fluff pulp of claim 1, wherein the fluff pulp has a carboxyl content greater than about 3.5 meq / 100 grams.
8. The fluff pulp of claim 1, wherein the fluff pulp has a copper ion content of about 0.7 ppm to 3.7 ppm by weight of the bleached kraft fiber.
9. The fluff pulp of claim 1, wherein the fluff pulp has an inhibition of ammonia formation of 22 ppm or less ammonia after 8 hours of subjecting the fluff pulp to an ammonia generation test in the absence of a super absorbent polymer (SAP), the ammonia generation test comprising the steps of: i) cutting the fluff pulp into 2 inch strips and fiberizing it using a Kamas H01 laboratory hammer mill to produce fiberized fluff pulp; ii) forming the fiberized fluff pulp into an airlaid mat having a diameter of 50 mm using an airlaid mat former; iii) each mat was made from 4 grams of fiberized fluff pulp and the mats were compressed in a carving press to a density of about 0.15 g / cc; iv) placing two compression pads in a sealed 1-liter bottle; v) adding 40 mL of a 1.0% urease solution (urease from Canavalia ensiformis (Jack Bean) purchased from Sigma) in freshly prepared synthetic urine (RICCA Chemical Company) to each 4 gram pad and sealing the bottle; and vi) The ammonia concentration in the head space of the bottle was measured using a Draeger tube.
10. A process for preparing the fluff pulp of claim 1, the process comprising: treating the bleached kraft fiber by adding about 0.2 ppm to about 50 ppm, based on the weight of the bleached kraft fiber, of copper or a salt thereof to produce the fluff pulp; wherein the fluff pulp inhibits ammonia formation by at least 50% more than a second bleached kraft fiber formed by the same process in the absence of copper.
11. The process according to claim 10, wherein the copper or its salt consists of one or more of: Elemental copper (Cu 0 ), copper (I) salts and copper (II) salts.
12. The process of claim 10, wherein the copper or its salt consists of: Elemental copper, copper (I) chloride, copper (I) oxide, copper (I) sulfate, copper (II) carbonate, copper (II) chloride, copper (II) phosphate, copper (II) nitrate, copper (II) perchlorate, copper (II) phosphate, copper (II) sulfate, copper (II) tetrafluoroborate, copper (II) trifluoromethanesulfonate, hydrates thereof, or combinations of any two or more thereof.
13. The process of claim 10, further comprising bleaching the kraft fiber using a multi-step bleaching process to produce bleached kraft fiber, wherein the treating occurs after the bleaching.
14. The process of claim 10, further comprising bleaching the kraft fiber using a multi-step bleaching process to produce bleached kraft fiber, wherein no additional bleaching is performed after said treatment.
15. The process of claim 10, wherein the fluff pulp does not include super absorbent polymer (SAP).
16. The process of claim 10, wherein the fluff pulp has a carboxyl content greater than about 3.5 meq / 100 grams.
17. The process of claim 10, wherein the fluff pulp further comprises iron ions.
18. The process of claim 17, wherein the fluff pulp comprises an iron ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
19. A process for improving the odor control properties of fluff pulp, the process comprising: treating the bleached kraft fiber by adding about 0.2 ppm to about 50 ppm, based on the weight of the lignocellulosic material, of copper or a salt thereof to produce the fluff pulp; wherein the fluff pulp inhibits ammonia formation by at least 50% more than a second treated lignocellulosic material formed by the same process in the absence of copper.
20. The process of claim 19, wherein the fluff pulp does not include super absorbent polymer (SAP).
21. The process of claim 19, wherein the fluff pulp comprises 0.7 ppm to 3.7 ppm copper ions based on the weight of the fluff pulp.
22. The process of claim 19, wherein the fluff pulp further comprises iron ions.
23. The process of claim 22, wherein the fluff pulp comprises an iron ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
24. The process of claim 10, comprising treating the bleached kraft fiber to produce the fluff pulp by adding from about 0.7 ppm to about 3.7 ppm copper or a salt thereof, based on the weight of the bleached kraft fiber.
25. The fluff pulp of claim 9, wherein the copper ions of the copper ion content comprise copper (I) salts, copper (II) salts, hydrates thereof, or combinations of any two or more thereof.
26. The fluff pulp of claim 9, wherein the copper ion content comprises one or more of elemental copper, copper (I) chloride, copper (I) oxide, copper (I) sulfate, copper (II) carbonate, copper (II) chloride, copper (II) phosphate, copper (II) nitrate, copper (II) perchlorate, copper (II) phosphate, copper (II) sulfate, copper (II) tetrafluoroborate, and copper (II) trifluoromethanesulfonate.
27. The fluff pulp of claim 9, wherein the fluff pulp further comprises iron ions.
28. The fluff pulp of claim 27, wherein the fluff pulp comprises an iron ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
29. The fluff pulp of claim 9, wherein the fluff pulp does not include super absorbent polymers (SAP).
30. The fluff pulp of claim 9, wherein the fluff pulp has a carboxyl content greater than about 3.5 meq / 100 grams.
31. A process for preparing the fluff pulp of claim 9, the process comprising: treating bleached kraft fiber by adding copper or its salt to the bleached kraft fiber to produce the fluff pulp; wherein the fluff pulp inhibits ammonia formation by at least 50% more than a second bleached kraft fiber formed by the same process in the absence of copper.
32. The process of claim 31 , wherein the copper or its salt consists of one or more of: Elemental copper (Cu 0 ), copper (I) salts and copper (II) salts.
33. The process of claim 31 , wherein the copper or a salt thereof consists of: Elemental copper, copper (I) chloride, copper (I) oxide, copper (I) sulfate, copper (II) carbonate, copper (II) chloride, copper (II) phosphate, copper (II) nitrate, copper (II) perchlorate, copper (II) phosphate, copper (II) sulfate, copper (II) tetrafluoroborate, copper (II) trifluoromethanesulfonate, hydrates thereof, or combinations of any two or more thereof.
34. The process of claim 31, further comprising bleaching the kraft fiber using a multi-step bleaching process to produce bleached kraft fiber, wherein the treating occurs after the bleaching.
35. The process of claim 31, further comprising bleaching the kraft fiber using a multi-step bleaching process to produce bleached kraft fiber, wherein no additional bleaching is performed after said treatment.
36. The process of claim 31 , wherein the fluff pulp does not include super absorbent polymer (SAP).
37. The process of claim 31 wherein the fluff pulp has a carboxyl content greater than about 3.5 meq / 100 grams.
38. The process of claim 31 wherein the fluff pulp further comprises iron ions.
39. The process of claim 38, wherein the fluff pulp comprises an iron ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
40. The process of claim 31, comprising treating the bleached kraft fiber to produce the fluff pulp by adding from about 0.7 ppm to about 3.7 ppm, by weight of the bleached kraft fiber, of copper or a salt thereof.
41. A process for preparing fluff pulp, the process comprising: treating the bleached kraft fiber by adding about 0.2 ppm to about 50 ppm, based on the weight of the bleached kraft fiber, of copper or a salt thereof to produce the fluff pulp; Wherein, the fluff pulp comprises bleached kraft fiber, and the bleached kraft fiber comprises: a length-weighted average fiber length of at least about 2 mm; a copper value of less than about 7; and An ISO level of at least 80; and A copper ion content of from about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber; wherein the fluff pulp inhibits ammonia formation by at least 50% more than a second bleached kraft fiber formed by the same process in the absence of copper.
42. The process of claim 41, wherein the copper or its salt consists of one or more of: Elemental copper (Cu 0 ), copper (I) salts and copper (II) salts.
43. The process of claim 41, wherein the copper or a salt thereof consists of: Elemental copper, copper (I) chloride, copper (I) oxide, copper (I) sulfate, copper (II) carbonate, copper (II) chloride, copper (II) phosphate, copper (II) nitrate, copper (II) perchlorate, copper (II) phosphate, copper (II) sulfate, copper (II) tetrafluoroborate, copper (II) trifluoromethanesulfonate, hydrates thereof, or combinations of any two or more thereof.
44. The process of claim 41, further comprising bleaching the kraft fiber using a multi-step bleaching process to produce bleached kraft fiber, wherein the treating occurs after the bleaching.
45. The process of claim 41, further comprising bleaching the kraft fiber using a multi-step bleaching process to produce bleached kraft fiber, wherein no additional bleaching is performed after said treatment.
46. The process of claim 41, wherein the fluff pulp does not include super absorbent polymer (SAP).
47. The process of claim 41 wherein the fluff pulp has a carboxyl content greater than about 3.5 meq / 100 grams.
48. The process of claim 41 wherein the fluff pulp further comprises iron ions.
49. The process of claim 48, wherein the fluff pulp comprises an iron ion content of about 0.2 ppm to about 50 ppm by weight of the bleached kraft fiber.
50. The process of claim 41, comprising treating the bleached kraft fiber to produce the fluff pulp by adding from about 0.7 ppm to about 3.7 ppm copper or a salt thereof, based on the weight of the bleached kraft fiber.
Citation Information
Patent Citations
Ligno cellulosic materials and the products made therefrom
CN101171389A
Modified cellulose from chemical kraft fiber and methods of making and using same
CN102459754A
Surface treated modified cellulose from chemical kraft fiber and methods of making and using the same
CN105228657A
Odor control pulp composition
CN116397456B
